DEK oncogene is overexpressed during melanoma progression. (7th March 2017) - Riveiro‐Falkenbach, Erica; Ruano, Yolanda; García‐Martín, Rosa M.; Lora, David; Cifdaloz, Metehan; Acquadro, Francesco; Ballestín, Claudio; Ortiz‐Romero, Pablo L.; Soengas, María S.; Rodríguez‐Peralto, José L.
Summary: DEK is an oncoprotein involved in a variety of cellular functions, such as DNA repair, replication, and transcriptional control. DEK is preferentially expressed in actively proliferating and malignant cells, including melanoma cell lines in which DEK was previously demonstrated to play a critical role in proliferation and chemoresistance. Still, the impact of this protein in melanoma progression remains unclear. Thus, we performed a comprehensive analysis of DEK expression in different melanocytic tumors. The immunostaining results of 303 tumors demonstrated negligible DEK expression in benign lesions. Conversely, malignant lesions, particularly in metastatic cases, were largely positive for DEK expression, which was partially associated with genomic amplification. Importantly, DEK overexpression was correlated with histological features of aggressiveness in primary tumors and poor prognosis in melanoma patients. In conclusion, our study provides new insight into the involvement of DEK in melanoma progression, as well as proof of concept for its potential application as a marker and therapeutic target of melanoma.